Building And Standardizing Leadership Personality Scale For Some Iraqi Soccer Premier League Clubs 2016 – 2017 from the Players and Administrators Point of View - Mohammed, Ismael; Abedul jabar, Mohammed (Journal of Physical Education, 2018)
Building And Standardizing Leadership Personality Scale For Some Iraqi Soccer Premier League Clubs 2016 – 2017 from the Players and Administrators Point of View The aim of the research is to build and standardize leadership personality scale for the coaches of the Iraqi Premier League clubs from the point of view of the players and administrators. Tests and measurements are essential elements for the evaluation process. The research problem was determining the level of leadership personality of coaches. The researcher used the deceptive method. The sample consisted of (468) players and administrators of the Iraqi premier League. And the researcher took the scientific steps required to obtain the scale in its final form, using the appropriate statistical means to achieve its objectives. The results showed that leadership personality consist of five fields thus resulted in many factors making a total of 38 items distributed across the five domains of the scale. The researcher recommended searching for coaches with leadership personality because of their importance in raising the level of the team.